Advances in the in vitro digestion and fermentation of polysaccharides. (27th August 2021) - Guo, Yuxi; Chen, Xuefeng; Gong, Pin; Chen, Fuxin; Cui, Dandan; Wang, Mengrao
Summary: In vitro digestion models are widely used to study the structural changes, digestion and release of food components under simulated gastrointestinal conditions. As compared to the in vivo digestion tests, the in vitro digestion reflects the digestion and utilisation of food after ingestion and has the advantages of being time consuming, inexpensive, reproducible and free from moral and ethical restrictions. This study reviewed the current research studies on the in vitro simulated digestion of polysaccharides conducted in the last 5 years and focused on the oral, gastric and intestinal digestion models, with the aim of providing a basis for the further testing of changes in the content, structure and active ingredients of polysaccharides before and after digestion. Abstract : Advances in the in vitro digestion and fermentation of polysaccharides.